Varian Paradigmatis dan Pengaruh Teori Kritis Dalam llmu Komunikasi - Erry, hadiati (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2007)
Science   communication in  ifs  early  years  start  from  science  positivism.Science communication paradigm  is   also   start  from   a   positive   empiric   methodoly matters. Shannon-Weaver  mechanistic  approach  states   that   communication  is mechanic pieces   human   do   which  basically  imitating  transmitter and   receiver machines.Communicationis a linear mechanisticprocess that comes  from derivation of  nature science    in human  behaviour cluster.  Some  of basic models  in science communication is a  matter of  full distention belween  researcher and  researchee. obiectivity-rnechanistic,     deductive-nomologic  and   factual  external  research  from eve,y symptom in human communicativebehaviour.      -Positivism  in  science   communication form   a   social  science   that  has authoritarianand negative characteristic, except for rules and system  that required·· corelational fest.  This paper  give  brief picture  an  alternative approach for communicationscience.Thereare  several arguments in public which cannot be explained  only  by numbers  and percentage.  Numbers  sometimes create  ideological missconcepfion. This articlefriesto develop feorificalapproach in a practicalframework.